Adaptive synchronization of quaternion-valued inertial neural networks with uncertain parameters and a flexible time delay: A novel non-separation and non-reduction approach - Yin, Xufan; Peng, Tao; Xiong, Jiang; Tu, Zhengwen; Li, Zuxiong; Wang, Liangwei (Nonlinear Analysis: Modelling and Control, 2026)
In this paper, a direct method is presented for analyzing the adaptive synchronization of quaternion-valued inertial neural networks (QVINNs) with uncertain parameters and time delay. By this method, the forms of time delays and the Lyapunov function in this paper are flexible, and in stability analysis, the requirement for negative definiteness of Lyapunov functions will be weakened. In addition, a more generalized adaptive synchronization controller has been proposed for QVINNs, which no longer requires multiple calculations of the control gain. Since most of the previous adaptive control methods did not impose requirements on the convergence speed of the QVINNs, a class of improved adaptive controllers is designed to address the slow synchronization speed of QVINNs. Finally, numerical simulations are conducted to validate the synchronization conditions.